Carbene-catalyzed α-carbon amination of chloroaldehydes for enantioselective access to dihydroquinoxaline derivatives - Huang, Ruoyan (2020)
An NHC-catalyzed α-carbon amination of chloroaldehydes was developed. Cyclohexadiene-1,2-diimines are used as amination reagents and four-atom synthons. Our reaction affords optically enriched dihydroquinoxalines that are core structures in natural products and synthetic bioactive molecules.